A portable and low-cost solution for real-time manipulation of the vestibular sense - Chen, Anthony; Kuo, Calvin; Blouin, Jean-Sébastien (Journal of neuroscience methods, 2022)
The vestibular system encodes head motion in space which is naturally accompanied by other sensory cues. Electrical stimuli, applied across the mastoid processes, selectively activate primary vestibular afferents which has spurred clinical and biomedical applications of electrical vestibular stimulation (EVS). When properly matched to head motion, EVS may also manipulate the closed-loop relationship between actions and vestibular feedback to reveal the mechanisms of sensorimotor recalibration and learning. We designed a portable, low-cost real-time EVS system using an Arduino microcontroller programmed through Simulink that provides electrical currents based on head angular motion. We used well-characterized vestibular afferent physiological responses to head angular velocity and electrical current to compute head-motion equivalent of real-time modulatory EVS currents. We also examined if our system induced recalibration of the vestibular system during human balance control. Our system operated at 199.997 Hz ( ± 0.005 Hz) and delivered head-motion-equivalent electrical currents with ∼10 ms delay. The output driving the current stimulator matched the implemented linear model for physiological vestibular afferent dynamics with minimal background noise (<0.2% of ± 10 V range). Participants recalibrated to the modulated closed-loop vestibular feedback using visual cues during standing balance, replicating earlier findings. EVS is typically used to impose external perturbations that are independent of one’s own movement. We provided a solution using open-source hardware to implement a real-time, physiology based, and task-relevant vestibular modulations using EVS. Our portable, low-cost vestibular modulation system will make physiological closed-loop vestibular manipulations more accessible thus encouraging novel investigations and biomedical applications of EVS. [Display omitted] •Electrical vestibular stimulation (EVS) activates vestibular afferents.•Our system generates EVS based on the physiology of the vestibular system.•Designed a portable system to modulate human vestibular sense in real-time.•Closed-loop manipulation of the vestibular sense induces vestibular recalibration.•Our system opens opportunities to reveal how we learn and interact with the world.